Tumour Behaviour of Low-Grade Papillary Urothelial Carcinoma: A Single-Centre Retrospective Study - Dutta, Satya (Cureus, 2021)
Background and objective Carcinoma of the urinary bladder is the most common urological cancer, and it accounts for 3.9% of all cancer cases in men. Patients with the subset of noninvasive low-grade papillary urothelial carcinoma (LG-UrCa) are at higher risk for tumour recurrence. In this study, we aimed to analyse the histopathological features of LG-UrCa and to correlate those with recurrence potential as well as disease stage and grade progression. Materials and methods We conducted a retrospective study from January 2016 to December 2018. All cases with presenting biopsy initially reported as LG-UrCa were included in the study. All cases with initial biopsy reported as high-grade papillary urothelial carcinoma (HG-UrCa) were excluded from the study. We used the 2016 World Health Organization/International Society of Urological Pathology (WHO/ISUP) guidelines for the classification of papillary urothelial neoplasm. Results A total of 48 initially diagnosed cases of LG-UrCa were identified. Two out of 48 cases were reclassified as high-grade urothelial carcinoma and were excluded from the study. The mean age of patients at presentation was 56.7 years. The mean duration of follow-up was 19.8 months. The mean size of initial tumours was 3.4 cm. Tumour recurrence was encountered in 14 (30.4%) of 46 patients. Out of the four patients who had high-grade progression (8.7%), two also developed TNM stage progression. These two patients eventually underwent radical cystectomy. Patients with larger initial tumour sizes were found to have an increased tumour recurrence rate (p=0.009). Patients with multiple lesions at initial diagnosis had a significantly higher tumour recurrence rate than those with a single tumour (p=0.02). There was no significant difference with regard to intravesical Bacillus Calmette-Guérin (BCG) and tumour recurrence (p=0.065). None of the clinicopathological parameters were significantly associated with the grade and/or stage progression. Conclusion Based on our findings, patients with larger initial tumour size and tumour multiplicity at presentation had an increased tumour recurrence rate.